Fetal echocardiography in Lithuania: traditions, significance and problems - VANKEVIČIENĖ, Ramunė (Acta medica Lituanica, 2010)
Background. The discovery of ultrasound has made a revolution in almost all fields of medicine. The past three decades have withessed an intensive development of fetal echocardiography methods and technique. The aim of the paper is to present a review of the results and trends of the last 10 years of fetal echocardiography in Lithuania and to show the spectrum and outcomes of prenatally detected congenital heart diseases. Materials and methods. Fetal echocardiography was performed for 1816 fetuses during the period from 1999 to 2009. Results. Cardiac pathology was diagnosed in 176 (9.7%) fetuses. Heart defects were detected in 112 (63.6%) of them, cardiac rhythm and conduction disturbances in 62 (35.2%), cardiomyopathy in 2 (1.1%) fetuses, and heart rhabdomyoma in 1 (0.6%) fetus. The general rate of the postnatal diagnosis of congenital heart defects in Lithuania was about 10%. Most of fetal cardiac diseases (70.5%) were diagnosed after 22 weeks of gestation. Because most of antenatally diagnosed congenital heart defects (74%) were critical and inconsistent with life, a large part of newborns (40.2%) died in the neonatal period, 10.7% of fetuses died in utero, and 8% of pregnancies were terminated by abortion. The data demonstrate good tendencies: the diagnosis has become earlier, a wider spectrum of diseases have been diagnosed, more newborns have survived. Our survey shows that 41.1% of newborns with prenatally diagnosed congenital heart defects have survived. Conclusions. 10% of severe congenital heart diseases are detected prenatally in Lithuania. The efficacy of antenatal diagnostics depends on the qualification of specialists, the number of tertiary care centers, on a successful collaboration among pediatric cardiologists, obstetricians and geneticists. The main problem is an insufficient preparation of obstetricians, the uncertified favor of pediatric cardiologist. Keywords: congenital heart disease, fetal echocardiography, antenatal diagnostics